Assessing the use of immersive virtual reality, mouse and touchscreen in pointing and dragging-and-dropping tasks among young, middle-aged and older adults. (November 2017) - Chen, Jiayin; Or, Calvin
Abstract: This study assessed the use of an immersive virtual reality (VR), a mouse and a touchscreen for one-directional pointing, multi-directional pointing, and dragging-and-dropping tasks involving targets of smaller and larger widths by young ( n = 18; 18–30 years), middle-aged ( n = 18; 40–55 years) and older adults ( n = 18; 65–75 years). A three-way, mixed-factorial design was used for data collection. The dependent variables were the movement time required and the error rate. Our main findings were that the participants took more time and made more errors in using the VR input interface than in using the mouse or the touchscreen. This pattern applied in all three age groups in all tasks, except for multi-directional pointing with a larger target width among the older group. Overall, older adults took longer to complete the tasks and made more errors than young or middle-aged adults. Larger target widths yielded shorter movement times and lower error rates in pointing tasks, but larger targets yielded higher rates of error in dragging-and-dropping tasks. Our study indicated that any other virtual environments that are similar to those we tested may be more suitable for displaying scenes than for manipulating objects that are small and require fine control. Although interacting with VR is relatively difficult, especially for older adults, there is still potential for older adults to adapt to that interface. Furthermore, adjusting the width of objects according to the type of manipulation required might be an effective way to promote performance. Highlights: Interacting with VR is relatively difficult for older users, but there is still potential for them to adapt to it. Overall, older adults were slower and made more errors in the HCI tasks than young and middle-aged adults. Larger targets yielded shorter times and fewer errors in pointing, but more errors in dragging-and-dropping.